SEM ANALYSIS OF ZIRCONIA-DENTAL MATERIAL - Elena-Raluca Baciu; Maria Bolat; Roxana Ionela Vasluianu; Dana-Gabriela Bosînceanu; Irina Grădinaru; Doriana Agop-Forna (Romanian Dental Association for Education, 2019)
In dentistry, zirconia is used as a framework for dental prostheses and has been traditionally covered with porcelain to provide excellent aesthetics. The purpose of this study is to evaluate the effects of surface polishing on the properties of zirconium dioxide (Zirconia), the Tizian material, from Schutz Dental. The microstructural tests were carried out using an electron scanning electron microscope, VegaTescan. The images show a more pronounced action of the felt and Al2O3 powder on the material compared to mechanical polishing by sandpapers. From the analysis of the distribution of the chemical elements we can see a good homogeneity, which leads to the maintenance of the chemical, physical and mechanical properties in all the areas of this material